Negotiating institutional transformation : a case study of gender-based change in a South African university - Shackleton, Lesley (Gender Studies, 2014)
This study contributes towards understanding the complex dynamics that are inherent in the transformation of institutional culture in the higher education environment in South Africa. Innovative use was made of gender-based change as a case study of social transformation in a case institution, the University of Cape Town. A feminist, qualitative approach was used to map gender as a component of institutional culture and to explore how the institution's culture influences the dynamics of gender-based change. A gendered lens was focused on three different sources of data: the leadership discourse from 28 years of annual Vice Chancellor's Reports, and interview and documentary data around two purposively selected feminist initiatives to further women's career development in the higher education environment. The integration of analyses of different types of data from these three sources proved to be a powerful tool for exposing contested meanings and highlighting discrepancies between the logic of the organization and experienced realities. My research corroborates numerous previous studies of universities worldwide and reveals the case institution to have a conservative, patriarchal culture. In addition to the formal hierarchical and collegial structures typical of many universities, aspects of the institutional culture that contribute towards its marked conservatism were identified. The analyses revealed how the hegemony of academic and androcentric discourses resulted in a culture which 'others' people into differently empowered groups and how this interacts with a dominant liberal discourse that values and privileges individualism. The resultant mystification is exhausting and confusing to those who are not part of the dominant group, and combines with fragmented understandings of purpose to stifle institutional change and thus strengthen conservatism. Beyond the male hegemony, the most significant aspect of the gendered institutional culture is the persistent vanishing of gender on the campus. There is little evidence of any ability to engage seriously with gender or any recognition that this might be a priority. The gender-based change initiatives that were studied were the result of spontaneous action of tempered radicals, insiders within the institution who felt alienated by aspects of its culture and thus were positioned also as outsiders. Both initiatives have resulted in successful programmes but an analysis of the dynamics around their establishment shows the power of the institutional culture to neutralize and de-politicize their impact on the gendered culture, despite the pervasiveness of the liberal discourse. I suggest that for change to succeed it is necessary to purposely reduce the power that the conservative institution can exert. This can be achieved by avoiding direct confrontation with the dominant patriarchal culture and by forging appropriate, sympathetic external alliances with those who have influence and access to resources. My research suggests that transformation of the institutional culture is unlikely to be led by those who, by conforming to the culture, have attained hierarchical leadership positions and are thus most threatened by change. Transformation is most likely to be brought about by those who question norms, seize opportunities and focus on small wins. The liberal discourse common to many universities leads to a tolerance of mavericks, and I suggest that this can provide opportunities to surface the silent voices that must inform debates around transformation. However I have revealed how resistant the sector can be to cultural change. My analyses have shown how even ostensibly very successful initiatives can be assimilated and how their ability to result in institutional change can be disempowered using political structures and micropolitics. Effecting transformation of the complex institutional culture in higher education will require a deep engagement with these powerful conservative forces.